Associations between the Framingham Risk Score and coronary plaque characteristics as assessed by three-vessel optical coherence tomography. Issue 6 (September 2016) - Vergallo, Rocco; Xing, Lei; Minami, Yoshiyasu; Soeda, Tsunenari; Ong, Daniel S.; Gao, Lei; Lee, Hang; Guagliumi, Giulio; Biasucci, Luigi M.; Crea, Filippo; Yu, Bo; Uemura, Shiro; et al.
Abstract : Objectives: This study sought to explore the association between the Framingham Risk Score (FRS) and coronary plaque characteristics assessed by optical coherence tomography (OCT) imaging. Background: Clinical prediction models are useful for identifying high-risk patients. However, coronary events often occur in individuals estimated to be at low risk. Methods: A total of 254 patients with coronary artery disease who underwent three-vessel OCT were divided into tertiles according to FRS. Nonculprit plaque characteristics were compared among the three groups. Results: A total of 663 plaques were analyzed. FRS was significantly associated with calcification [37% (low FRS) vs. 46% (intermediate FRS) vs. 70% (high FRS); P <0.001] and neovascularization [39% (low FRS) vs. 41% (intermediate FRS) vs. 56% (high FRS); P <0.001], but not with lipid-rich plaques or thin-cap fibroatheroma (TCFA). On multivariate analysis, FRS was an independent predictor of the presence of both calcification and neovascularization. There were no deaths, two acute myocardial infarctions, and 15 nontarget lesion revascularizations at the 1-year follow-up. The event rate increased progressively across FRS tertiles [2.4% (low FRS) vs. 7.1% (intermediate FRS) vs. 8.6% (high FRS); P =0.186]. The c -statistic for FRS to predict future clinical events was 0.628 (95% confidence interval, 0.500−0.757). The addition of both calcification and TCFA to FRS provided incremental prognostic value [ c -statistics: 0.761 (95% confidence interval, 0.631−0.890)]. Conclusion: The present study showed significant associations between FRS and the presence of coronary calcification and neovascularization in nonculprit plaques. The combination of FRS and OCT-detected calcifications and TCFA provides improved prognostic ability in identifying patients with known coronary artery disease who are at risk of recurrent events. Abstract : Supplemental Digital Content is available in the text.